Do drought and understory beech interact to influence the nutrition and growth of sugar maple? - Parsons, William F. J.; Ghotsa Mekontchou, Claudele; Shovon, Tanvir Ahmed; Maheu, Audrey; Rivest, David (Frontiers in Forests and Global Change, 2025)
Hardwood forests dominated by sugar maple (Acer saccharum) at its northern limit (Quebec) are threatened by rising regional temperatures and recurrent summer drought. In a rainfall exclusion experiment, we imposed artificial drought in six maple stands where American beech (Fagus grandifolia) saplings proliferated in the understory (with overstory beech presence) or were absent. Two paired plots were established in sites where beech proliferated vs. those that were beech-free, i.e., covered by rainfall excluders vs. left uncovered for summer 2021 and 2022. Responses to the four resulting treatments were subjected to Bayesian analysis. Dendroclimatological estimates of annual basal area increment (BAI) produced by three canopy maples within 12 plots, together with foliar nutrients of the same mature maple trees and soil nutrient pools (ion-exchange probes, with increasing burial duration), were compared across plots. Comparisons included ordination scores for foliage (DCA1, Detrended Correspondence Analysis) and Principal Component Analysis (PCA: PC1 and PC2) for soils. Soil water content (SWC) beneath excluders was 56% of adjacent rainfall-accessible plots; beneath understory beech saplings, this deficit negatively affected maple BAI, but only in 2022. Diagnosis and Recommendation Integrated System (DRIS) indices indicated foliar Mg insufficiency and Ca sufficiency. Mg insufficiency increased with rainfall exclusion, regardless of beech sapling presence. Rainfall exclusion reduced soil nutrient supply levels relative to controls; some supply rates (total pools, PC1, PC2, acidity) progressively increased over probe burial duration (2021: 14–56 days) in a diffusion-dependent manner under excluders, while reaching a plateau (equilibrium-dependent adsorption) with accessible rainfall. NO3-N progressively dominated beech-free soil inorganic-N pools over time, which diminished regardless of rainfall exclusion. Likewise, soil base cations (Ca + Mg + K) remained high in beech’s absence, and vice versa for acidity (Al + Fe + Mn). Modest rainfall manipulations decreased BAI, altered adsorption processes, and shifted soil pools from endo- to ectomycorrhizal dominance. Even short-term moisture deficiency in maple soils may incur further stress in already nutrient-stressed stands, initiating nutrient cycle uncoupling between foliar and soil pools.